Cone Beam Computed Tomography Analysis of Crestal Cortical Bone Thickness at Implant Site in Relationship with Crestal Soft Tissue Thickness - Saoud, Qaid Hussein Mohammed (University of Science and Technology, Sana’a, 2026)
The success of dental implantology is highly dependent on the quality and quantity of the host bone and the surrounding soft tissues. While crucial, the relationship between crestal cortical bone thickness (CCBT) and crestal soft tissue thickness (CSTT) remains underexplored, particularly within specific populations like Yemen. This study aims to analyze this relationship using Cone Beam Computed Tomography (CBCT) in a selected Yemeni population. A retrospective cross-sectional study was conducted on 399 CBCT scans meeting specific inclusion criteria. Scans were analyzed using Invivo Dental 5 software to measure CCBT and CSTT at various implant sites across the jawbones. Demographic data (age, gender) and edentulous site location were recorded. Statistical analysis was performed using SPSS version 26, employing Mann-Whitney, Kruskal-Wallis, logistic regression, and Pearson's correlation tests. The study revealed that Mandibular anterior sites demonstrated the highest mean values for both CSTT (2.24 ± 0.74 mm) and CCBT (1.79 ± 0.80 mm), whereas maxillary posterior sites showed the lowest CCBT (1.15 ± 0.23 mm). Moreover, the findings evealed a statistically significant positive correlation between CSTT and CCBT (r = 0.362, p < 0.01). Significant variations were found based on gender and anatomical site. Males exhibited greater CSTT and CCBT than females. This study confirms a significant relationship between crestal cortical bone and overlying soft tissue thickness in the Yemeni population. The findings highlight substantial site-specific and gender-based anatomical variations. These results provide crucial, population-specific data that can enhance preoperative planning, risk assessment, and the development of tailored implant protocols to improve clinical outcomes in implant dentistry for this demographic.
Keywords: Cone Beam Computed Tomography; Crestal Cortical Bone Thickness; Oral Surgery; Implantology; Sana'a